Advances in acoustics and vibration II : proceedings of the Second International Conference on Acoustics and Vibration (ICAV2018), March 19-21, 2018, Hammamet, Tunisia /: proceedings of the Second International Conference on Acoustics and Vibration (ICAV2018), March 19-21, 2018, Hammamet, Tunisia. ([2019]) - Unknown
No abstract available